Teacher's Use of English and Spanish Interactive Strategies during Wordless Shared Book Reading: Relations to Emergent Bilingual Children's Responses - Natalia M. Rojas; Gigliana Melzi; Adina Schick (MDPI AG, 2024)
Little attention has been paid to describing the ways early childhood education (ECE) teachers implement interactive strategies and the use of Spanish and English, in real time, to support Spanish-English emergent bilingual children's contributions to shared book reading interactions. Video recordings from 19 ECE classrooms during shared book reading were used to conduct sequential analysis to examine the different types of interactive strategies (e.g., questions, extensions) implemented by bilingual ECE teachers and emergent bilinguals' responses to these strategies. This study found that teachers' interactive strategies may reflect a degree of reciprocity, with teachers and children sensitively attuned to one another's contributions in real time. Teachers' questions in English and Spanish were related to emergent bilinguals' responses across a wide range of language complexity. Similarly, teachers and emergent bilinguals tended to respond to one another in the language of the prior utterance, suggesting teachers and emergent bilinguals are attuned to the contributions of one another. By examining teacher-child dynamics, this study produced results that can address issues that may have direct, translatable implications for ECE practice and intervention efforts.